Estudo experimental dos mecanismos resistentes de juntas com chave de cisalhamento em ligações pilar-viga - Faleiros Junior, José Herbet (2018)
In this dissetation exploratory models are used to examine the behavior of semi - rigid pillar - beam connections with shear key. This type of connection is ordinary in Brazil prefabricated concrete structures. Thus, the use of a solenoid, shear key between the pillar - beam face and the addition of negative reinforcement on the cap rod, being this at the top of the beam, gives the connection a semi - rigid behavior and the possibility of transferring vertical actions relieving the amount of effort in the console. The work contributes to verify the structural situation and the representativeness of the connections already performed in Brazil, since there are no studies or tests carried out to verify the real influence of impact of the shear key assists in the composition of the bond. The study consisted in the creation of a simple model, based on long-term experiments in Brazil for semi-rigid connections. Through the tests, it was verified the efficiency of the participation of the shear key, where they were considered models of real magnitude. This study will serve as a basis for the later realization of joint geometry variation, as well as the real problem in beams with large deformations. The study is finished by isolating the total portion resisted by the semi-rigid connection by discounting the value resisted by the pin effect of the negative rod and the portion of stresses resisted by the console, in this way it was determined that the shear key actually had a relief effect of 40,88% of the total amount of efforts.